THERAPEUTIC POTENTIAL OF WHITE HOREHOUND EXTRACT IN COUNTERACTING CHEMOTHERAPY-INDUCED THYMIC DAMAGE IN RATS - Rasulova Nafisa Rashidovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Chemotherapy is effective against tumors but often damages the thymus, impairing T-lymphocyte maturation and immune function. This study evaluated the protective effect of White Horehound (Marrubium vulgare) extract on chemotherapy-induced thymic alterations in 4-month-old albino rats. Rats with DMBA-induced skin carcinoma were divided into control, chemotherapy, and chemotherapy plus White Horehound groups. Morphometric and histological analyses revealed that chemotherapy reduced thymic capsule and trabecular thickness, shortened trabeculae, altered vascular dimensions, and decreased thymocyte and lymphocyte numbers. Post-chemotherapy administration of White Horehound extract partially restored these parameters, improved structural organization, and normalized thymic cellular composition. These findings indicate that White Horehound extract exerts a corrective effect on chemotherapy-induced thymic damage, highlighting its potential as a plant-based biocorrective agent to support immune function during cytotoxic therapy.